Effect of Pregnane X Receptor*1B genetic polymorphisms on postoperative analgesia with fentanyl in Chinese patients undergoing gynecological surgery. Issue 1 (December 2016) - Yuan, Jing-Jing; Ma, Xiao-Jing; Li, Zhi-Song; Chang, Yan-Zi; Zhang, Wei; Kan, Quan-Cheng; Hou, Jun-Kai; Zhang, Li-Rong
Abstract Background The purpose of the study was to investigate the effects of the pregnane X receptor(PXR)*1B polymorphisms on CYP3A4 enzyme activity and postoperative fentanyl consumption in Chinese patients undergoing gynecological surgery. Methods A total of 287 females of Han ethnicity, aged 20 to 50 years old, ASA I or II, scheduled to abdominal total hysterectomy or myomectomy under general anesthesia were enrolled. The analgesic model used was fentanyl consumption via patient-controlled intravenous analgesia (PCIA) in the post-operative period. Additionally, pain was assessed using a visual analog score (VAS). Pain scores, occurrence of adverse reactions and consumption of fentanyl were recorded during the 24 h postoperative period. The enzyme activity of CYP3A4 was evaluated by measuring the plasma ratio of 1′-hydroxymidazolam to midazolam 1 h after intravenous administration of 0.1 mg/kg midazolam. PXR genotyping was performed by direct DNA sequencing and thePXR * 1B haplotype was analyzed via PHASE V.2.1 software. Results The polymorphism frequency ofPXR11156A  > C/11193 T > C and 8055C > T were 49.6 and 49.3%, and the rate ofPXR * 1B haplotype was 48.8% in our study. None of the pain scores, consumption of fentanyl 24 h post-operatively or enzyme activity of CYP3A4, showed differences among different genotypes. Conclusions PXR11156A > C, PXR11193T > C, PXR8055C > T or thePXR * 1B haplotype do not appear to be important factors contributing to CYP3A4 activity and interindividual variations in postoperative fentanyl consumption in Han female patients undergoing gynecological surgery. Trial registration The DNA samples were obtained since 2007 to 2010 year in our hospital, there was no registration at that time. So this section is not applicable to our research.